ASSESSMENT OF SAURIDA TUMBIL (BLOCH) STOCK IN THE NORTHWEST CONTINENTAL SHELF WATER OF INDIA - GULATI, D. K.; DEVARAJ, M.; GEORGE, J. P. (Journal of Indian Fisheries Association, 2015)
Based on the data collected from New Ferry Wharf, Sassoon Dockand exploratory survey of MFV Saraswati on the Northwest coast ofIndia, the growth, mortality, population and stock parameters ofSaurida tumbil is reported in the present communication. The VonBertalanffy growth function (VBGF) parameters for growth on lengthwere found to beL== 49.8 em, K = 0.96/year, to= -.141 year. The lengthat recruitment Or) is 80 mm. (tr = .167 year) while the length at firstcapture (lc) for the commercial trawl fishery is 100 mm (tc = 0.25 year).The annual fishing mortality coefficient (F) for 1983-85 was 0.43, thenatural mortality coefficient (M) was 1.33 and the exploitation ratio(E) was 0.25. The yield per recruit (YIR) attained the maximum of 54.99gat F = 1.091 forE = 0.45 for the present tc at 0.25 year. The annualtotal stock (P) and standing stock (P) in the exploitation portion at theinshore grounds to a depth of about 50 m were estimated to be 12,811tons and 6,034 tons respectively. The average annual yield of 2,635tons at the present F = 0.439 (E = 0.247) was less than the maximumsustainable yield (MSY) for 3,331 tons attainable from the inshoregrounds at E = 0.45.